Calculus Cholecystitis Concomitant With Cavernous Portal Vein in a Woman: A Case Report (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Both open and laparoscopic cholecystectomy for chronic calculus cholecystitis concomitant with a cavernous portal vein is challenging. However, laparoscopic cholecystectomy was reported as time consuming and more troublesome for profuse intraoperative haemorrhage.  Hospitals' constraints on tools, extraordinary expertise, and funds, which are common in Bangladesh, increase the risk of dealing with such cases. However, in such situations, open cholecystectomy may be a safe, timesaving, cost-effective option.Case Presentation: On 2nd November 2019 performed an open cholecystectomy on such a patient at Chevron Specialist Hospital, Chattogram where, initially, there was difficulty in delineating the bile duct, cystic duct, and cystic artery because of the overlying dilated cavernous portal vein. However, it was evident after aspiration of the gallbladder and acritical view. Subsequently, we completed the cholecystectomy safely, spending sixty-five minutes with approximately fifty ml of blood loss. The recovery was uneventful, and the patient had no complaints at regular follow-ups for four years. The relevant laboratory and imaging findings were normal, but the cavernous portal vein persisted.Conclusion: Open cholecystectomy for calculus cholecystitis coincided with cavernous portal vein, performed with patience and great caution with standby vascular surgeons and tools, was safe, time-saving, and cost-effective in the limitation of facilities, funds, and experienced laparoscopic surgeons.JCMCTA 2024 ; 35 (1) : 167-171